Clinical course of multiple sclerosis-associated uveitis: a retrospective series of 49 cases - William Gil; Sabine Mainbourg; Robin Jacquot; Ludovic Trefond; Louis Olagne; Pierre Clavelou; Sébastien Trouillier; Antoine Bardy; Marc Andre; Géraldine Androdias-Condemine; Caroline Vasseneix; Laurent Kodjikian; et al. (Journal of Ophthalmic Inflammation and Infection, 2026)
Abstract Background The temporal relationship between uveitis and neurological relapses in multiple sclerosis (MS)–associated uveitis is poorly documented; and MS-targeted disease-modifying therapies (DMTs) may influence the ocular course. Objective To evaluate the temporal relationship between uveitis and neurological relapses in MS-associated uveitis, and to assess the impact of MS treatments on uveitis outcomes. Methods This is a retrospective multicenter study. Uveitis cases were identified from the “Lyon Uvéite” cohort, EDMUS (European Database for Multiple Sclerosis), and open calls for case reporting. Inclusion criteria were: age ≥ 18 years, MS according to McDonald criteria, and uveitis confirmed by an ophthalmologist. Uveitis and neurological flares were considered concomitant if they occurred within a three-month interval. The probability of uveitis relapse was compared between MS-targeted DMTs and uveitis-directed therapies using Kaplan–Meier survival analysis. Results 49 patients were included, with a median follow-up of 19 years [10–25]. Uveitis and neurological relapses were dissociated in 94.2% of cases. In recurrent-event analyses accounting for time-varying treatment exposure, MS-targeted disease-modifying therapies were associated with a lower risk of uveitis relapse compared with uveitis-directed therapies (adjusted HR 0.20, 95% CI [0.08–0.54], p = 0.002). Conclusions MS-associated uveitis appeared largely dissociated from neurological disease activity. MS-targeted disease-modifying therapies were associated with fewer uveitis relapses, although these exploratory findings require confirmation in prospective studies.